2008
DOI: 10.1177/0956247808096124
|View full text |Cite
|
Sign up to set email alerts
|

“Negotiated spaces” for representation in Mumbai: ward committees, advanced locality management and the politics of middle-class activism

Abstract: In Mumbai, new forms of cooperation between local government and citizens seek to improve local representation and the quality of services. This paper examines which residents are represented or excluded in these arrangements, the mandates and processes by which the arrangements are negotiated and the outcomes. Local representation through elected councillors is compared with that through voluntary neighbourhood groups (Advanced Locality Management groups, or ALMs), which work with the executive wing of local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 10 publications
1
71
0
2
Order By: Relevance
“…40 See note 24. Also see Baud and Nainan (2008) for an example of a similar, but less extreme, program in Mumbai, where neighborhood associations are delegated responsibilities for local waste management. Mumbai's ward committees are far more functional and representative than Delhi's, making the risk of gentrified participation less extreme there.…”
Section: Resultsmentioning
confidence: 99%
“…40 See note 24. Also see Baud and Nainan (2008) for an example of a similar, but less extreme, program in Mumbai, where neighborhood associations are delegated responsibilities for local waste management. Mumbai's ward committees are far more functional and representative than Delhi's, making the risk of gentrified participation less extreme there.…”
Section: Resultsmentioning
confidence: 99%
“…Coelho and Cornwall (2006) indicate that 'more contingent factors can alter the balance of power, such as unintended consequences of mutations and processes of politicisation that accompany resource negotiations or subtle shifts that new discourses of rights, social justice and citizenship create as they circulate through networks that support different social actors and expand their interpretive and political horizons'. Recent research on India found that negotiating rights through 'political spaces' was more effective for vulnerable low-income groups, while negotiating rights through 'executive spaces' was more effective for middleclass citizens (Baud & Nainan 2008). Linking with the political strategies of the growing middle-classes and their resident associations is also suggested as a viable alternative (Chakrabarti 2008).…”
Section: Impacts Of Invited Spaces On Influence and Political Rightsmentioning
confidence: 99%
“…Furthermore, strategies and outcomes are often very much related to the motivation of the mayor or leading group within the council and the nature and scope of groups drawn into budgeting processes (Cabannes 2004;Mitlin 2004a). Recent research in India indicates elite capture of the (metropolitan) governance agenda through middle-class activism of residents or neighbourhood associations (Baud & Nainan 2008;Chakrabarti 2008). A fundamental problem with promoting participation in 'invited spaces' is that often, entrenched relations of dependency, fear and dispriviledge undermine the possibility of the kind of deliberative decision-making they are to foster (Cornwall 2004a).…”
mentioning
confidence: 99%
“…As such it was an explicit attempt to move beyond expert-driven policy-making [34,39,40] that often offers little space for "local knowledges". The underlying logic is that the gap between citizens and institutions can be bridged by giving space to citizens or locals to exercise voice and influence policy and institutions [41,42]. As such, it is an attempt to balance "bureaucratic procedures and local practices" [31].…”
Section: Participationmentioning
confidence: 99%